Nanorefrigerants application possibilities study to increase the equipment ecological-energy efficiency - Лукьянов, Николай Николаевич; Хлиева, Ольга Яковлевна; Железный, Виталий Петрович; Семенюк, Юрий Владимирович (Eastern-European Journal of Enterprise Technologies, 2015)
The results of experimental and theoretical studies of the TiO2 and Al2O3 nanoparticle additives in the working fluid R600a / mineral oil on the eco-energy efficiency of the compressor system have been considered. The experimental setup (refrigeration compressor system) and the experimental methodology have been described. Following working fluids have been selected for compressor refrigeration system: R600a / compressor oil; R600a / compressor oil / nanoparticle TiO2 (1,0 and 0,48 wt%.) and R600a / compressor oil / nanoparticles Al2O3 (0,52 and 0,08 wt.%). The results of experimental studies of cooling capacity, compressor power and coefficient of performance at the different values of working fluid flow rate in the compressor refrigeration system have been reported. It was shown that the nanoparticle additives may lead to increase in energy consumption of the compressor system up to 23% at flow rate of the working fluid equal to 0.00025 kg/s at the evaporator temperature 258 K. The method of eco-energy analysis has been proposed to science-based evaluation of an expediency of nanoparticle additives to the refrigeration equipment working fluids. This method is based on assessment of total equivalent greenhouse gases emissions on the equipment life cycle (TEGHGE). Expressions to assessment the value of TEGHGE and the specific eco-indicator have been proposed. The values of TEGHGE and eco-indicator on the life cycle of the compressor system based on experimental data obtained for the cooling capacity and compressor power for different working fluids have been analyzed. It was shown that Al2O3 nanoparticle additives with 0.52 % mass concentration provide the best eco-energy effect.